TRANSFORMING VISITOR EXPERIENCES IN UZBEKISTAN’S CULTURAL TOURISM THROUGH VIRTUAL AND AUGMENTED REALITY (Spectrum Journal of Innovation, Reforms and Development, 2024)
This paper explores how virtual reality (VR) and augmented reality (AR) can transform cultural tourism in Uzbekistan. Drawing on global market dynamics and experiential learning theory, it analyzes how immersive technologies enhance visitor motivation, engagement, and emotional connection. The study highlights that while Uzbekistan possesses significant cultural resources, fragmented implementation of VR/AR limits their impact. Integration within a coherent framework could strengthen competitiveness by creating immersive narratives, digitally reconstructing heritage, enriching cultural landscapes, and engaging diaspora audiences. The paper concludes that VR and AR, if strategically deployed, can reposition Uzbekistan as a leading hub for cultural tourism in Central Asia.